Underemployment in the informal sector of Kampala District - Byandaga, Livingstone (Kampala, 1996)
Unpublished thesis (M.A., EPP.) - Makerere University, 1996.
Includes bibliographical references.
Keywords: Underemployment -- Kampala District -- Uganda; Informal sector (Economics) -- Uganda